Lithium Niobate Electro-Optic Racetrack Modulator Etched in Y-Cut LNOI Platform - Mohamed Mahmoud; Lutong Cai; Christian Bottenfield; Gianluca Piazza (IEEE Photonics Journal, 2018)
An electro-optic modulator (EOM) based on a racetrack resonator coupled to a waveguide using butterfly multi-mode interference (MMI) coupler is fabricated on Y-cut lithium niobate (LN) thin film. This is the first demonstration of a LN EOM in which the thin film of LN is etched in a Y-cut substrate using chlorine-based inductively coupled plasma reactive ion etching, a process, which is readily compatible with semiconductor fabrication facility. The Y-cut LNOI platform is interesting for the integration of electro-optic and acousto-optic components, since differently from any other LN cut it facilitates taking advantage of the maximum electro-optic and piezoelectric coefficients of LN. Coupling to the racetrack was enabled using a butterfly MMI coupler, which offered operation near the critical coupling condition, hence increasing the extinction ratio (ER) of the modulator. An unloaded quality factor of 1.3 × 105 was extracted for this device, which is equivalent to a propagation loss of 2.3 dB/cm. Modulation bandwidth of 4 GHz, wavelength tuning rate of 0.32 pm/V, and an ER of more than 10 dB were experimentally measured for the EOM.